Motivational Orientation, Boredom and Fun in Physical Education: The Mediation Role of Self-Esteem and Motor Self-Efficacy. - Reigal, Rafael E.; Hernández-Martos, Jacobo; Monteiro, Diogo; Pérez-López, Rocío; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica (Perceptual & Motor Skills, 2024)
Adolescents who enjoy physical education (PE) classes are more likely to be active during out-of-school hours. Similarly, achievement goal theory suggests that task-oriented motivation is associated with higher levels of reported fun during PE classes. In contrast, ego-oriented motivation has been related to boredom in class, but some self-perceptions (e.g., self-esteem or motoric self-efficacy) may modify this relationship and are important for physical activity. Our aim in this paper was to analyze the relationships between motivational orientation and fun and boredom in PE classes by assessing the mediating effects of self-esteem and self-efficacy. We surveyed 478 teenagers between 13 and 18 years of age (M = 14.57; SD = 1.15) with the Task and Ego Orientation in Sport Questionnaire (TEOSQ), the Rosenberg Self-Esteem Scale (RSE), the Motor Self-Efficacy Scale (MSES), and the Intrinsic Satisfaction in Sport Scale (SSI-EF). We used a structural equation model to evaluate relationships between these variables of interest. We found a positive relationship between ego orientation and boredom and between task orientation and fun; and we found a negative relationship between task orientation and boredom in PE classes. Importantly, we observed indirect effects from self-esteem and motoric self-efficacy in the relationships between motivational orientation and boredom and fun in PE. These results highlight the importance of students' motivational orientations in PE classes and illustrate that self-perception of self-esteem and motoric self-efficacy can mediate these relationships.